Natural Products as Mechanism‐based Anticancer Agents: Sp Transcription Factors as Targets. (7th July 2016) - Safe, Stephen; Kasiappan, Ravi
Abstract : Naturally occurring anticancer agents and their derivatives act on multiple pathways to inhibit carcinogenesis and their inhibition of migration, invasion, growth, survival, and metastasis is associated with downregulation of genes associated with these responses. Several phytochemical‐derived anticancer drugs including curcumin, betulinic acid, phenethylisothiocyanate and celastrol, and many others induce reactive oxygen species, and their effects on gene regulation show some overlap in various cancer cell lines. We hypothesize that reactive oxygen species‐inducing anticancer agents and many other natural products target a common pathway in cancer cells, which initially involves downregulation of specificity protein 1 (Sp1), Sp3, and Sp4, which are highly expressed in tumors/cell lines derived from solid tumors. This hypothesis is supported by several published reports showing that a large number of phytochemical‐derived anticancer agents downregulate Sp1, Sp3, Sp4, and pro‐oncogenic Sp‐regulated genes involved in cell growth (cyclin D1 and growth factor receptors), survival (bcl‐2 and survivin), angiogenesis and migration (MMP‐9, vascular endothelial growth factor and its receptors), and inflammation (NF‐kB). The contribution of this pathway to the anticancer activity of drugs such as curcumin, celastrol, betulinic acid, and phenethylisothiocyanate must be determined in order to optimize clinical applications of drug combinations containing these compounds. Copyright © 2016 John Wiley & Sons, Ltd.